Pharmaceutical and personal care products-induced stress symptoms and detoxification mechanisms in cucumber plants. (March 2018) - Sun, Chengliang; Dudley, Stacia; Trumble, John; Gan, Jay
Abstract: Contamination of agricultural soils by pharmaceutical and personal care products (PPCPs) resulting from the application of treated wastewater, biosolids and animal wastes constitutes a potential environmental risk in many countries. To date a handful of studies have considered the phytotoxicity of individual PPCPs in crop plants, however, little is known about the effect of PPCPs as mixtures at environmentally relevant levels. This study investigated the uptake and transport, physiological responses and detoxification of a mixture of 17 PPCPs in cucumber seedlings. All PPCPs were detected at higher concentrations in roots compared to leaves, with root activity inhibited in a dose-dependent manner. At 5–50 μg/L, the mature leaves exhibited burnt edges as well as a reduction in photosynthesis pigments. Reactive oxygen species (ROS) production and lipid peroxidation increased with increasing PPCP concentrations; and their contents were greater in roots than in leaves for all PPCP treatments. Enzymes involved in various functions, including oxidative stress (superoxide dismutase and ascorbate peroxidase) and xenobiotic metabolism (peroxidase and glutathione S-transferase), were elevated to different levels depending on the PPCP concentration. Glutathione content gradually increased in leaves, while a maxima occurred at 0.5 μg L −1 PPCPs in roots, followed by a decrease thereafter. This study illustrated the complexity of phytotoxicity after exposure to PPCP mixtures, and provided insights into the molecular mechanisms likely responsible for the detoxification of PPCPs in higher plants. Graphical abstract: Highlights: Physiological, biochemical and molecular methods were used to assess PPCP-induced stress symptoms and detoxification mechanisms. Oxidative stress response reflected the intensity of PPCP treatment and sensitivity of plant species to PPCPs. Enzymes responsible for various functions, including oxidative stress and xenobiotic metabolism, were elevated to detoxify PPCPs' toxicity. Abstract : Plants detoxify PPCPs through enhanced antioxidant defense and increased xenobiotic-metabolizing enzyme activities.